MENAKAR OTENTISITAS DAN KUALITAS KONTEN TAFSIR AL-QUR’AN DI RUANG DIGITAL: Analisis Penafsiran Nadirsyah Hosen di Instagram - Ujang Abduloh Mahpud; Muhammad Habib Izzuddin Amin (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
The development of digital da’wah, particularly Qur’anic interpretation on social media platforms such as Instagram, has provided broad access to Islamic teachings while simultaneously raising serious challenges regarding authenticity and scholarly quality. Moderate figures like Nadirsyah Hosen (@nadirsyahhosen_official) have become prominent in presenting Qur’anic interpretation on Instagram; however, specific studies on the authenticity and quality of his interpretations on this platform remain limited. This study aims to analyze the authenticity and quality of Qur’anic interpretation presented by Nadirsyah Hosen on his Instagram account. This research employs a qualitative method with a content analysis approach. The primary data consist of three selected posts from @nadirsyahhosen_official, chosen purposively and analyzed based on parameters of authenticity (fidelity to authoritative Islamic sources) and quality (methodology, relevance, and argumentation). The findings indicate that Nadirsyah Hosen’s interpretations maintain strong authenticity, as evidenced by consistent references to the Qur’an, hadith, and classical scholars’ views. In terms of quality, his approach predominantly combines maudhu’i (thematic) and contextual methods, articulated through poetic and Sufi-inspired language. Hosen successfully translates classical theological concepts into responses to contemporary digital-age issues, such as the crisis of meaning and challenges to faith arising from social media dynamics. This study concludes that Hosen’s Qur’anic interpretations on Instagram represent a model of digital da’wah that effectively integrates scholarly authenticity with communicative quality, resulting in content that is relevant, aesthetically engaging, and transformative for the digital audience.